2010
DOI: 10.1182/blood-2010-03-275628
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets for endoplasmic reticulum stress-induced apoptosis in B-CLL

Abstract: Apoptosis-based anticancer therapies require an in-depth understanding of the apoptotic machinery components of malignant cells, not only apoptotic regulators but also apoptotic executioners, given that their expression levels and functional integrity strongly determine the efficacy of therapeutic treatments. 2,3 Apoptosis is mediated by caspases, a conserved family of aspartate-specific cysteine proteases that are activated by several pathways. 4 The intrinsic mitochondrial pathway relies on caspase-9 as init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 47 publications
(144 reference statements)
9
61
0
Order By: Relevance
“…The function of GRP78 in the hematopoietic system is just emerging, however, recent study clearly revealed involvement of GRP78 in hematopoietic stem cell survival and lymphogenesis (Wey et al 2012a). In addition, it has been shown that GRP78 expression is up-regulated in various forms of human leukaemia and implicated as causative factor for therapeutic resistance and early relapse (Tanimura et al 2009;Rosati et al 2010;Uckun et al 2011;Wey et al 2012b). In our experiments, we have detected GRP78 to be expressed in non-treated HL-60 cells and treatment of the cells with NaBu for 48 hours was associated with decrease of GRP78 level.…”
Section: Discussionsupporting
confidence: 56%
“…The function of GRP78 in the hematopoietic system is just emerging, however, recent study clearly revealed involvement of GRP78 in hematopoietic stem cell survival and lymphogenesis (Wey et al 2012a). In addition, it has been shown that GRP78 expression is up-regulated in various forms of human leukaemia and implicated as causative factor for therapeutic resistance and early relapse (Tanimura et al 2009;Rosati et al 2010;Uckun et al 2011;Wey et al 2012b). In our experiments, we have detected GRP78 to be expressed in non-treated HL-60 cells and treatment of the cells with NaBu for 48 hours was associated with decrease of GRP78 level.…”
Section: Discussionsupporting
confidence: 56%
“…23 Importantly, CLL cells have a functional ER stress-associated apoptotic signaling, and are susceptible to both pharmacologic and genetic ER targeting strategies. 24,25 Based on all the above observations and our previous findings that GSI I increased CLL cell apoptosis and inhibited Notch activation, 9 we investigated whether an inhibited proteasome activity and an increased ER stress signaling are also involved in GSI I-induced CLL cell apoptosis, and examined how these events and Notch inhibition contribute to this apoptosis. Clarifying the effects of GSI I on these three critical regulators of CLL cell survival may be important to design more effective therapies for this leukemia.…”
Section: Chronic Lymphocytic Leukemia (Cll) Is Characterized By Accummentioning
confidence: 99%
“…CD38 surface expression and ZAP-70 intracellular expression in CLL cells were examined as previously described. 24,29 Supporting Information Table 1 gives clinical laboratory characteristics and the Binet stage of CLL patients.…”
Section: Cll Clinical Laboratory Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations